Single Cell Resolution of Chronic Graft-Versus-Host Disease - Boiko, Julie Renee (My University, 2024)
Chronic graft-versus-host disease (cGVHD) remains a frequent and morbid outcome of allogeneic hematopoietic cell transplantation (HCT). Simply put, in cGVHD, the donor-derived immune system attacks healthy recipient tissue. Preceding tissue damage mediated by chemoradiotherapy and alloreactive T cells compromise central and peripheral tolerance mechanisms, leading to aberrant donor T cell and germinal center B cell differentiation, culminating in pathogenic macrophage infiltration and differentiation in target tissue, with ensuant fibrosis. This process results in a heterogeneous clinical syndrome frequently requiring prolonged immunosuppressive therapy.The first portion of this dissertation addresses the clinical problem that immune pathway-targeted cGVHD agents have sustained efficacy in only a minority of patients. This suggests that different patients’ cGVHD may be dominated by different immune pathways, and it would thus be beneficial to specifically discern druggable, dysregulated immunity. We used single cell RNA sequencing-based approaches in our informative preclinical cGVHD models to “reverse engineer” temporal IL-17 and CSF-1 signatures in mouse blood that could be used to interrogate patients. We defined distinct, non-intuitive IL-17 and CSF-1 signatures in mouse blood monocytes that could be identified in monocytes from approximately 50% of patients at the time of cGVHD diagnosis. These signatures can now be evaluated in clinical studies to help delineate potential responder and non-responders to therapeutics targeting these respective cGVHD pathways. The second portion considers the relationships of hematopoietic and non-hematopoietic cells in mediating cGVHD skin pathology. In lichenoid cGVHD patient skin biopsies, we conducted high-resolution spatial transcriptomics to dissect the geographical dimensionality of immune networks. We demonstrated varying degrees of immune cell infiltration characterized by T cells and previously unappreciated CSF-1R+ mononuclear cell subsets. Proximity analyses demonstrated adjacent monocyte-derived CSF1RintLYZhi macrophages and CD8+ T cells in juxtaposition to the keratinocyte layer. Keratinocytes in highly immune cell-infiltrated cGVHD skin showed fundamental profile changes associated with antigen presentation and immune cell recruitment. Furthermore, hematopoietic and nonhematopoietic cell gene expression and proximity analyses suggested high levels of epithelial-mesenchymal transition within keratinocytes and macrophage-mesenchymal transition within skin fibroblasts. These high resolution data highlight CSF-1R+ macrophage subsets as the early sine qua non lesion in human cutaneous cGVHD, with profound and previously unappreciated downstream effects on local keratinocyte and fibroblast differentiation that represent novel therapeutic targets.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: Immunology; Molecular medicine and mechanisms of disease